La breve historia del juicio político en las constituciones del México independiente; (1824-1917) - Valencia Damián, Christopher (Universidad Michoacana de San Nicolás de Hidalgo, 2022)
This research work is a historical study of the evolution of the legal figure of the political trial in the Federal Constitutions of our country, taking as a starting point the independence of Mexico; first with the Federal Constitution of 1824, followed by the centralist period of the Seven Constitutional Parties of 1836 and the Organic Bases of 1843. Later, the Constitutive and Reform Act of 1847, would definitively bury centralism in Mexico. With the restoration of Federalism, the Constitution of 1857 would establish the bases for the Fundamental Law of 1917, which currently governs us. Similarly, other institutions of great importance for the Mexican political system were studied, such as the inviolability of opinions for the deputies and senators of the Republic, the political jurisdiction as a prerogative for high-level public officials, as well as the constitutional procedure for the purpose of withdrawing the state of procedural-criminal exception through the judgment of provenance.

El presente trabajo de investigación es un estudio histórico de la evolución de la figura jurídica del juicio político en las Constituciones Federales de nuestro país, tomando como punto de partida la independencia de México; primero con la Constitución Federal de 1824, seguido al periodo centralista de las Siete Partidas Constitucionales de 1836 y a las Bases Orgánicas de 1843. Mas tarde, el Acta Constitutiva y de Reformas de 1847 sepultara de forma definitiva el centralismo en México. Con la restauración del Federalismo, la Constitución de 1857 establecería las bases para la Ley Fundamental de 1917, misma que actualmente nos rige. De igual forma, se estudiaron otras instituciones de gran importancia para el sistema político de México, como la inviolabilidad por opiniones para los diputados y senadores de la Republica, el fuero político como una prerrogativa para funcionarios públicos de alto nivel, así como el procedimiento constitucional para efecto de re- tirar el estado de excepción procesal penal mediante el juicio de procedencia.
Facultad de Derecho y Ciencias Sociales. Maestría en Derecho
Keywords: info:eu-repo/classification/cti/5; FDCS-M-2022-0971; Ciencias políticas; Juicio de procedencia; Control; Poder; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/8460